2020
DOI: 10.1002/pat.4994
|View full text |Cite
|
Sign up to set email alerts
|

Robust cellulose nanofibrils reinforced poly(methyl methacrylate)/polystyrene binary blend composites with pebble‐shaped structure using Pickering emulsion gel

Abstract: Both poly(methyl methacrylate) (PMMA) and polystyrene (PS) have excellent transparency, but a blend of the two typically has low mechanical properties and poor transparency owing to phase separation. Herein, oil-in-water Pickering emulsion gel technology was combined with the hot pressing process to prepare cellulose nanofibrils (CNFs) reinforced PMMA/PS binary blend composite film materials (CNFs/PMMA/PS). The CNFs/PMMA/PS composites with a pebble-shaped structure had a unique three-dimensional crosslinked ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Generally, the broad peak observed at around 20°corresponds to the ordered chains of PS, [45] while the peak at 30.2°corresponds to PMMA. [46] Apart from these peaks, all other peaks were correlated with the crystalline nature of KTO. All observed peaks (2θ = 11.6°, 14.1°, 18.8°, 28.1°, 33.4°, 35°, 43°, 47°, 54.5°, 57.9°and 67°) matched with reported peaks of pure KTO.…”
Section: Xrd Analysis Of Pmma/ps/kto Polymer Blendsmentioning
confidence: 97%
“…Generally, the broad peak observed at around 20°corresponds to the ordered chains of PS, [45] while the peak at 30.2°corresponds to PMMA. [46] Apart from these peaks, all other peaks were correlated with the crystalline nature of KTO. All observed peaks (2θ = 11.6°, 14.1°, 18.8°, 28.1°, 33.4°, 35°, 43°, 47°, 54.5°, 57.9°and 67°) matched with reported peaks of pure KTO.…”
Section: Xrd Analysis Of Pmma/ps/kto Polymer Blendsmentioning
confidence: 97%
“…28,29 It has previously been demonstrated that simple casting of Pickering emulsions does not result in sufficient mechanical strength because of the agglomeration of CNFs. 30–32 To the best of our knowledge, electrospinning of PHBH incorporated CNF has never been reported. This study focused on the electrospinning of Pickering emulsion to prepare CNF-incorporated fibres.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Among the various applications of PS are foam packaging, food packaging, cups, disposable plates, silverware, cassettes, and CDs. [18][19][20][21] However, when it comes to safety, the range of PS applications in some areas is limited because of its restricted thermal stability and high flammability. Therefore, some research groups have recently devoted their efforts to enhance the thermal stability of PS.…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily blow molded, extruded, or injected, thus, these features make it a very valuable manufacturing polymer 15–17 . Among the various applications of PS are foam packaging, food packaging, cups, disposable plates, silverware, cassettes, and CDs 18–21 . However, when it comes to safety, the range of PS applications in some areas is limited because of its restricted thermal stability and high flammability.…”
Section: Introductionmentioning
confidence: 99%